Monitoring Jaringan dan Notifikasi dengan Telegram pada Dinas Komunikasi dan Informatika Kota Padang - Nanda Fernando; Humaira; Ervan Asri (SOTVI - Society of Visual Informatics, 2020)
Handling of network problems at Dinas Komunikasi dan Informatika Kota Padang is still done conventionally. This conventional method has several weaknesses, among others: the process of finding out slow network problems, information on problematic network conditions is conveyed using voice calls from smartphones, the slow network checking process and inefficient use of time. From this problem, a system for network handling that utilizes information technology is developed called Network Monitoring by implementing the Cacti and Telegram software functions. The result of this research is a network monitoring system based on web browser and mobile by implementing Cacti with SNMP features as network monitoring and Telegram as notification. The aim is to reduce weaknesses in the handling and repair of the network that has been used in Dinas Komunikasi dan Informatika Kota Padang